Cost-Effectiveness Analysis of 23-Valent Pneumococcal Polysaccharide Vaccine Program for the Elderly Aged 60 Years or Older in Shanghai, China - Xiaodong Sun; Yuekun Tang; Xiaoying Ma; Xiang Guo; Zhuoying Huang; Jia Ren; Jing Qiu; Hongli Jiang; Yihan Lu (Frontiers Media S.A., 2021)
Background: The pneumococcal vaccine has been considered as the most effective measure to prevent pneumococcal diseases. In 2013, Shanghai launched a major public health program to vaccinate people aged 60 years or older with 23-Valent Pneumococcal Polysaccharide Vaccine (PPSV-23) free of charge. By the end of June 2020, a total of 1.56 million old people had been vaccinated free of charge.Objective: To evaluate the cost-effectiveness of PPSV-23 vaccination program in Shanghai from the health system perspective.Methods: According to the actual number of people aged 60 years or older with PPSV-23 vaccination in Shanghai from 2013 to 2018, a multi-cohort Markov model for life-time was developed to compare health and economic outcomes of vaccinated people vs. if they were not vaccinated for PPSV-23. Cost effectiveness was reported as incremental cost effectiveness ratio (ICER). A 5% discount rate was used for both costs and health outcomes. In addition, one-way sensitivity analysis was used to test the model's robustness.Results: By the end of 2018, a total of 1,091,967 people aged 60 years or older were vaccinated with PPSV-23 in Shanghai, China. Comparing with the unvaccinated circumstances, PPSV-23 vaccination would cost US $19.62 million more and receive an additional 10,321.3 quality-adjusted life-year (QALY). PPSV-23 was associated with the ICER of $190.1 per QALY gained. The Results were sensitive to the variation of vaccine effectiveness against community-acquired pneumonia (CAP), and disease incidence, mortality, and costs of CAP. In all sensitivity analysis, the PPSV-23 was economical.Conclusion: The PPSV-23 vaccination program in Shanghai was cost-effective. With the further development of the project, the administrative costs of the vaccine will be reduced, making it more cost-effective.